Chemotherapy Toxicity in Elderly Population ≥65 Years: A Tertiary Care Hospital Experience from India - Mittal, Aditi; Agrawal, Amit; Batra, Sandeep; Dodagoudar, Chandragouda; Qureshi, Suhail (Indian Journal of Medical and Paediatric Oncology, 2019)
Context: Trials in the elderly have established that older individuals may benefit from chemotherapy to the same extent as younger individuals. Although the elderly patient is a prototype for cancer, very few clinical trials focus on the therapeutic decisions most directly facing older adults. Aims: This study was undertaken to study the chemotherapy-induced severe toxicity among elderly. Settings and Design: This study was a prospective, observational cohort study. The study commenced in October 2014 after obtaining clearance from the hospital ethics and protocol committee. Subjects and Methods: A total of 100 patients were included in the study. All patients were of age ≥65 years, had malignancy, and were planned to start with chemotherapy. Development of Grade 3/4/5 nonhematologic (NH) or Grade 4/5 hematologic (H) toxicities was taken as the development of severe toxicity. Statistical Analysis Used: The quantitative variables were expressed as a mean ± standard deviation and compared using unpaired t-test. P < 0.05 was considered statistically significant. Results: Overall, 64 (64%) patients were able to complete their prescribed treatment. Forty-four patients (44%) of our study cohort experienced Grade 4 H or Grade 3/4 NH toxicity. The most common H Grade 4 toxicities were neutropenia (6%) and thrombocytopenia (5%). The most common NH toxicities were fatigue (18%), infection (10%), and cardiac abnormalities (4%). Conclusions: Less than 50% of elderly patients experience severe chemotherapy-related toxicity. First 30 days are most important for toxicity assessment as 45% of patients experienced toxicity in this time frame.
Keywords: Chemotherapy; elderly; hematologic; nonhematologic; toxicity